Biomarkers for diagnosis and prognosis of myelin oligodendrocyte glycoprotein antibody-associated disease - review article - Sapana, Tamang; Zhuo, Zhihong (Frontiers in Immunology, 2025)
Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is a complex inflammatory central nervous system disorder affecting mainly children and young adults. Its diverse clinical spectrum often resembles other neurological diseases like multiple sclerosis (MS) or neuromyelitis optica spectrum disorder (NMOSD). Accurate diagnosis and monitoring are challenging due to its heterogeneous presentation and lack of specific biomarkers. In addition, disease-modifying therapies are well-established for treating MS and NMOSD. In contrast, the absence of approved therapies for MOGAD remains a significant challenge in clinical management and should become a priority in future research efforts. This review explores existing literature on biomarkers in MOGAD, including clinical, radiological, and laboratory parameters along with novel biomarkers and the future challenges that can facilitate personalized therapeutic approaches in MOGAD. A comprehensive understanding of these biomarker profiles is crucial for optimizing patient care and advancing therapeutic strategies in neuroinflammatory disorders.